Global women's health: current clinical trials in low‐ and middle‐income countries. (January 2015) - Merriel, A; Harb, HM; Williams, H; Lilford, R; Coomarasamy, A
<x xml:space="preserve">Abstract</x> Background Clinical trials in low‐ and middle‐income countries (LMICs) are necessary to develop evidence‐based approaches to improve women's health. Understanding what research is currently being conducted will allow the identification of research gaps, avoidance of duplication, planning of future studies, collaboration amongst research groups, and geographical targeting for research investments. Objectives To provide an overview of active women's health trials in LMICs. Search strategy The World Health Organization's International Clinical Trials Registry Platform was searched for trials registered between 1 April 2012 and 31 March 2014. Selection criteria Selected trials were randomised, conducted in LMICs, active, and with a women's health intervention or a significant outcome for the woman. Data collection and analysis Two reviewers extracted data. Analysis included geographical spread, speciality areas, pre‐enrolment registration, study size, and funders. Main results Of the 8966 records, 509 were eligible for inclusion. Gynaecology trials made up 57% of the research, whereas the remaining 43% of trials were in obstetrics. Research activity focused on fertility (17%), the antenatal period (15%), benign gynaecology (14%), intrapartum care (9%), and pre‐invasive disease and cancers (8%). The majority of trials (84%) took place in middle‐income countries (MICs). In low‐income countries (LICs) 83% of research investigated obstetrics, and in MICs 60% of research investigated gynaecology. Most trials (80%) had a sample size of 500 or fewer participants. The median size of trials in LICs was 815 compared with 128 in MICs. Pre‐enrolment registration occurred in 54% of trials. The majority (62%) of trials were funded locally. Authors' conclusions Many LMICs are active in women's health research. The majority of registered trials are located in MICs; however, the trials in LICs are often larger. The focus of research in MICs may be driven by local priorities and funding, with fertility being highly researched. In LICs, pregnancy is the focus, perhaps reflecting the international prioritisation of maternal health.